Distribution of Phototrophic Purple Nonsulfur Bacteria in Massive Blooms in Coastal and Wastewater Ditch Environments - Hiraishi, Akira; Nagao, Nobuyoshi; Yonekawa, Chinatsu; Umekage, So; Kikuchi, Yo; Eki, Toshihiko; Hirose, Yuu (Microorganisms (Basel), 2020)
The biodiversity of phototrophic purple nonsulfur bacteria (PNSB) in comparison with purple sulfur bacteria (PSB) in colored blooms and microbial mats that developed in coastal mudflats and pools and wastewater ditches was investigated. For this, a combination of photopigment and quinone profiling, pufM gene-targeted quantitative PCR, and pufM gene clone library analysis was used in addition to conventional microscopic and cultivation methods. Red and pink blooms in the coastal environments contained PSB as the major populations, and smaller but significant densities of PNSB, with members of Rhodovulum predominating. On the other hand, red-pink blooms and mats in the wastewater ditches exclusively yielded PNSB, with Rhodobacter, Rhodopseudomonas, and/or Pararhodospirillum as the major constituents. The important environmental factors affecting PNSB populations were organic matter and sulfide concentrations and oxidation–reduction potential (ORP). Namely, light-exposed, sulfide-deficient water bodies with high-strength organic matter and in a limited range of ORP provide favorable conditions for the massive growth of PNSB over co-existing PSB. We also report high-quality genome sequences of Rhodovulum sp. strain MB263, previously isolated from a pink mudflat, and Rhodovulum sulfidophilum DSM 1374T, which would enhance our understanding of how PNSB respond to various environmental factors in the natural ecosystem.